The Czech renewable energy and CO2 abatement in the context of the European Green Deal - Valerianová, Lenka; Burlakov, Georgi; Kotrba, Vojtěch; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2021)
Recently, the COVID-19 pandemic, combined with already existing efforts to combat global warming, allowed for an unprecedented amount of EU financing to be allocated for replacing conventional sources of energy with renewable ones, makes it essential for the decision makers to know what total social impact these policy actions have. As there currently is a little research done for the Czech Republic aiming at estimating benefits against costs of the Czech government programs stimulating the investments in renewable-energy production capacity for the whole period in which these programs are carried out and with methodology specifically designed to be compatible with such studies already made for other leading European economies, this thesis applies such a methodology in order to estimate the cost of the above mentioned actions as measured by the estimation of government expenditures on green energy subsidies decreased by the cost savings incurred by not using conventional energy sources. The research shows, that the Czech CO2 abatement costs are much lower compared to Italian and German ones, in case of wind even turning the social cost into social benefit. Moreover, it is shown that the net costs of wind and photovoltaic energy production are not predominantly driven by the output volume and the feed in tariff level, but rather by the prices of European Union Allowances and fossil fuels.
Vedoucí práce: Georgi Burlakov
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses